Increase Learning Motivation and English Speaking Skills through Cooperative Learning Management with Discovery Learning Model and Buzz-Tapps Technique - Syaharuddin, Syaharuddin (LPPM Universitas Bina Sarana Informatika, 2024)
Increasing learning motivation and English-speaking skills is a major concern in today's learning context. This research explores innovative approaches in the management of cooperative learning by utilizing the Discovery Learning model and Buzz-Tapps technique. This research aims to improve students' learning motivation and English-speaking skills. Another goal is to improve students' English-speaking skills. Cooperative learning with the Discovery Learning model and Buzz-Tapps technique is designed to strengthen students' ability to communicate effectively in English. With a focus on interaction between students and the use of discovery methods, this learning model seeks to create an environment that arouses student interest and engagement in the learning process. Cooperative learning management, this approach incorporates the principles of cooperative learning management, where students work together in small groups to achieve shared learning goals. Collaboration between students encourages more active and student-oriented learning. The Buzz-Tapps technique, in addition, is designed to strengthen communication and speaking skills through structured and focused practice. Through the Discovery Learning model, students are given the opportunity to discover and understand English concepts independently through hands-on experience and exploration. This approach encourages problem-solving, experimentation, and reflection to deepen students' understanding. This study discusses the implementation and impact of this approach in increasing learning motivation and English-speaking skills, and provides practical implications for education practitioners.